METHODOLOGY OF DEVELOPMENT OF PRACTICAL SKILLS OF STUDENTS IN LEARNING DRAWING GEOMETRY (American Journal of Pedagogical and Educational Research, 2024)
The main goal of developing students' practical skills in the teaching of drawing geometry is to help them to coordinate and apply this knowledge in practice, rather than to study the topics of drawing geometry theoretically. As practical skills are developed, students understand how to apply sketch geometry to real-life situations and learn to use this knowledge through practical problem solving, graph solving, plotting, and other practical activities.